Mental toughness as a mediator between sports psychological skills and athlete burnout: a buffering model - Zhang, Zhao; Yu, Shaoran (Frontiers in Psychology, 2025)
IntroductionAthlete burnout is a critical issue in competitive sports, yet the mechanisms linking sports psychological skills to burnout remain under-explored. This study has proposed a mental toughness-mediated buffering model to address this gap.MethodsData from 341 collegiate athletes were analyzed using hierarchical regression and Hayes’ PROCESS marco 3.5 (Model 4) with 5000 bootstrap samples for mediation effects.ResultsKey findings have shown that: (1)Sports psychological skills negatively predicted all three burnout dimensions (reduced sense of accomplishment, devaluation, and emotional/physical exhaustion); (2)Mental toughness partially mediated the effects of sports psychological skills on devaluation (β = −0.135, 95%CI[−0.249, −0.026]) and reduced sense of accomplishment (β = −0.159, 95%CI[−0.261, −0.062]). (3) However, no significant mediation effect was observed for emotional/physical exhaustion, suggesting distinct pathological mechanisms for this dimension.DiscussionThese results have advanced existing burnout theories by demonstrating dimension-specific mediation pathways, highlighting the need for targeted mental toughness interventions to mitigate devaluation and reduced sense of accomplishment in collegiate athletes.